Retaining knowledge workers for effective digital transformation - Yuen, Yee Yen; Chew, Yuan Zhang; Teoh, Wendy Ming Yen (Innovative Research Publishing, 2024)
The purpose of this research is to examine key factors affecting knowledge worker’s retention for digital transformation. This research is motivated by recent statistics that show that more than 70% of small and medium enterprises (SMEs) have yet to undergo large-scale digital transformation due to the failure to retain knowledge workers who can collect and disseminate information effectively through the application of digital technology. Although it is widely recognized that the knowledge worker is an important asset for the digital transformation of SMEs, there is a dearth of studies that focus specifically on how to retain knowledge workers in Malaysia. This research adopts a quantitative research design. Questionnaires were distributed to 200 respondents in SMEs in central urban cities in Malaysia. Purposive sampling was used to collect data where the respondents needed to fulfill criteria such as being currently working in SMEs and their job scope being related to idea generation, information handling, digital transformation, and strategic planning. This study discovers unique findings, such as that, compared to compensation, training and development, work environment, and work-life balance; they play a more significant role in motivating knowledge workers to stay in SMEs post-COVID-19 pandemic, which can enrich the literature on knowledge worker’s retention in developing countries. Serving as one of the pioneer studies in Malaysia and Southeast Asia that focuses on examining important factors to retain knowledge workers in SMEs post-COVID-19 pandemic, this finding benefits SME practitioners and policymakers in devising effective strategies to retain knowledge workers for effective digital transformation.